Inactivation of cefoxitin and moxalactam by Bacteroides bivius beta-lactamase. - Malouin, F (1986)
Moxalactam and cefoxitin are known for their high stability against Bacteroides beta-lactamases. We investigated the beta-lactamase activity of crude extracts obtained from three strains of Bacteroides bivius and two strains of Bacteroides fragilis against cefoxitin and moxalactam. In a spectrophotometric antibiotic assay with a 24-h incubation period, B. bivius extracts decreased the initial concentration (10 micrograms/ml) of moxalactam and cefoxitin by 60%, whereas B. fragilis extracts had no effect. In a microbiological assay, when B. bivius or B. fragilis extracts were added to cephalothin (10 micrograms/ml) or cefamandole (4 micrograms/ml), we observed complete disappearance of the inhibitory zones against the indicator strain (Clostridium perfringens ATCC 13124). Only the B. bivius extracts were able to decrease the inhibitory activity (from 10 to 100%) of cefoxitin and moxalactam (each at 10 micrograms/ml). Prior addition of clavulanic acid to crude extracts prevented the losses of antibacterial activity. Furthermore, the inhibition of the beta-lactamase hydrolysis of nitrocefin by cefoxitin or moxalactam was prevented by a 12-h preincubation of the beta-lactam with the B. bivius extracts but not with the B. fragilis extracts. Finally, with the B. bivius strain producing the most beta-lactamase, we showed an effect of inoculum size on the MICs of cefoperazone, cefoxitin, and moxalactam with a broth dilution technique. Increasing the inoculum size with the B. fragilis strains had no effect on the MISs of cefoxitin and moxalactam. These results indicate a slow and clavulanate-sensitive beta-lactamase activity of B. bivius extracts against cefoxitin and moxalactam.